Detection and Characterization of Microplastics in Two Major Lakes of Nepal: Begnas and Phewa - Gurung, Monika; Basyal, Sudeeksha; Pakhrin, Reema Lama; Pandit, Rashika; Dahal, Yubraj; Thapa, Bijay; Adhikari, Bikash (NPRC Journal of Multidisciplinary Research, 2025)
The widespread use and poor management of plastics are harming the environment. As plastics degrade, they break down into tiny particles smaller than 5mm, known as microplastics (MPs), which have become a growing environmental concern. In Nepal, very few studies have focused on MPs.This study investigates the sources, identification, and quantity of MPs, including their color and shape, in Begnas Lake and Phewa Lake, Nepal, using a slightly modified National Oceanic and Atmospheric Administration (NOAA) protocol. Visual microscopy confirmed the presence of fibers and fragments in samples collected from both lakes. Overall, in Phewa Lake, MPs concentrations ranged from 0.56 ± 0.17 to 2.46 ± 1.66 particles/L, while in Begnas Lake, they ranged from 1.07 ± 0.27 to 1.33 ± 0.51 particles/L. Further studies on exposure and potential health risks are needed. Thus, this study indicates the prospective baseline data of MPs research in Nepal’s lake water.